Much ado about very little? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Trade, especially the international variety, rarely brings out the best in people. Competition can be savage and when economic survival is at stake, slashing prices will work better than even the most creative advertising. It s an ugly...